Different oral manifestations of langerhans cell’s histiocytosis: report of two cases - Joana Leticia Vendruscolo; Fernanda Joly Macedo; Cleverson Patussi; Laurindo Moacir Sassi (Revista Sul-Brasileira de Odontologia, 2022)
Langerhans Cell Histiocytosis (LCH) is a disorder characterized by abnormal proliferation of CD1a+/S-100/CD207+ Langerhans cells. It has a peak of incidence between one and three[1]year-old, with a prevalence in males than females. It may affect several anatomical locations. Objective: to report two cases of oral manifestations of HCL, which exemplify the broad age range affected by the disease and its different clinical presentations. Material and methods: This is a retrospective, descriptive, observational study in the format of a technical note, represented by two clinical cases that demonstrates the different Oral Manifestations of Langerhans Cell’s Histiocytosis. Case report: a 47-year-old man presenting ulcerated lesions in hard palate and gingival region and a three-year-old boy with a diffuse swelling at the posterior mandible were diagnosed with HCL at the same institution. Conclusion: the HCL can manifest itself as a single lesion or as a multisystemic and potentially fatal disease. The clinician should be attentive to diagnose it at an early stage, to avoid worse complications and sequelae to the patient.